Approach for Intellectual Potential Analysis of the Scientific Institution - F. F. Yusifov (Цифровая трансформация)
An assessment of the intellectual potential of scientific personnel on the platform of electronic demography was carried out. The current situation in the field of forming population registers, conducting demographic studies, as well as a number of works related to the use of new sources of information and big data have been studied. Analyzed studies cover the assessment of human resources, the intellectual potential of the country and issues of scientific migration. To determine the factors influencing the intellectual potential of countries, an analysis of trends in demography and economic activity of the population, the level of education, the system of training and its financing was made. In order to monitor and predict scientific activity in accordance with the existing potential, to conduct analytical and statistical analysis, a Unified Electronic Information System on Scientific Personnel has been created. The article analyzes the intellectual potential of scientific personnel based on registry data on scientific personnel, which are clustered using the k-means method, which is a machine learning algorithm. Based on the results obtained, data on age groups, academic degrees, universities and the number of scientific publications were studied. Subsequent studies will take into account the issues of scientific productivity and scientific migration, which are of great importance in terms of assessing the country’s intellectual potential.